Common Cryoneurolysis Targets in Pain Management: Indications, Critical Anatomy, and Potential Complications - Sailer, Anne; Latich, Igor; Levey, Alexa O. (Seminars in Interventional Radiology, 2025)
Pain is a complex interplay of psychological, immunological, and sensory experiential factors that leads to discomfort and physical suffering unique to each person. Uncontrolled pain greatly affects quality of life, a person's ability to function in society, and often results in increased healthcare costs. In order to appropriately treat a patient, knowledge of the different types of pain and various combinations of therapies is imperative. Cryoneurolysis is an important adjunctive therapy in pain management. When used in the appropriate clinical setting, it can decrease a patient's pain, opioid consumption, and improve quality of life. This article reviews common targets for cryoneurolysis based on patient pathology and discusses anatomic considerations to ensure the most efficacious and safe patient outcomes.
Keywords: cryoneurolysis; cryoablation; nerve block; ganglion; interventional radiology